PAR4 (Protease-Activated Receptor 4) Antagonism With BMS-986120 Inhibits Human Ex Vivo Thrombus Formation. Issue 2 (February 2018) - Wilson, Simon J.; Ismat, Fraz A.; Wang, Zhaoqing; Cerra, Michael; Narayan, Hafid; Raftis, Jennifer; Gray, Timothy J.; Connell, Shea; Garonzik, Samira; Ma, Xuewen; Yang, Jing; Newby, David E.
Abstract : Objective—: BMS-986120 is a novel first-in-class oral PAR4 (protease-activated receptor 4) antagonist with potent and selective antiplatelet effects. We sought to determine for the first time, the effect of BMS-986120 on human ex vivo thrombus formation. Approach and Results—: Forty healthy volunteers completed a phase 1 parallel-group PROBE trial (Prospective Randomized Open-Label Blinded End Point). Ex vivo platelet activation, platelet aggregation, and thrombus formation were measured at 0, 2, and 24 hours after (1) oral BMS-986120 (60 mg) or (2) oral aspirin (600 mg) followed at 18 hours with oral aspirin (600 mg) and oral clopidogrel (600 mg). BMS-986120 demonstrated highly selective and reversible inhibition of PAR4 agonist peptide (100 μM)-stimulated P-selectin expression, platelet-monocyte aggregates, and platelet aggregation ( P <0.001 for all). Compared with pretreatment, total thrombus area (μm 2 /mm) at high shear was reduced by 29.2% (95% confidence interval, 18.3%–38.7%; P <0.001) at 2 hours and by 21.4% (9.3%–32.0%; P =0.002) at 24 hours. Reductions in thrombus formation were driven by a decrease in platelet-rich thrombus deposition: 34.8% (19.3%–47.3%; P <0.001) at 2 hours and 23.3% (5.1%–38.0%; P =0.016) at 24 hours. In contrast to aspirin alone, or in combination with clopidogrel, BMS-986120 had no effect on thrombus formation at low shear ( P =nonsignificant). BMS-986120 administration was not associated with an increase in coagulation times or serious adverse events. Conclusions—: BMS-986120 is a highly selective and reversible oral PAR4 antagonist that substantially reduces platelet-rich thrombus formation under conditions of high shear stress. Our results suggest PAR4 antagonism has major potential as a therapeutic antiplatelet strategy. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02439190. Abstract : Supplemental Digital Content is available in the text.